2020
DOI: 10.1007/s12079-020-00585-0
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Prostanoid Receptors: Expression, Characterization, Regulation, and Mechanism of Action

Abstract: Prostaglandin signaling controls a wide range of biological processes from blood pressure homeostasis to inflammation and resolution thereof to the perception of pain to cell survival. Disruption of normal prostanoid signaling is implicated in numerous disease states. Prostaglandin signaling is facilitated by G‐protein‐coupled, prostanoid‐specific receptors and the array of associated G‐proteins. This review focuses on the expression, characterization, regulation, and mechanism of action of prostanoid receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 201 publications
0
29
0
Order By: Relevance
“…Previous studies have shown that the EP3 receptor modulates multiple intracellular signaling pathways by coupling different types of heterotrimeric G proteins [ 29 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the EP3 receptor modulates multiple intracellular signaling pathways by coupling different types of heterotrimeric G proteins [ 29 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, HPLC-MS/MS analysis of eicosanoids was performed in our study, in order to compare the release of these lipid signaling molecules from epithelial (parental) and transformed cells with the mesenchymal phenotype. Although the production of several eicosanoids with anti-inflammatory and pro-resolution activities, such as lipoxin LXA4 [32], PGD2, and PGJ2 [37], was increased in the transformed cells, a massive increase in prostaglandins and HETEs with pro-carcinogenic and pro-inflammatory effects, especially PGE 2 [27], was observed. For example, 12-HETE and 20-HETE have been implicated in cell proliferation, inhibition of apoptosis, angiogenesis, and invasion/metastasis [38].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous lipid species, including sphingolipids and eicosanoids, have been shown to play important roles in carcinogenesis, both as lipid signaling molecules and as modulators of the structure/functions of cell membranes [20,31,32]. This study aimed: (1) to compare the SL and GSL content in the human bronchial epithelial cell line HBEC-12KT and in their BaP-transformed counterpart, HBEC-12KT-B1 cells with acquired mesenchymal status [30], in order to identify possible links between SL/GSL concentrations and the expression of genes related to SL/GSL metabolism; (2) to compare SL/GSL composition in exosomes released from both cell lines and to explore possible relationships between the SL/GSL profiles in exosomes and the mesenchymal epithelial cell phenotype, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO produces vasodilation by stimulat-ing soluble guanylate cyclase, leading to an increase in cyclic guanosine monophosphate (cGMP) [83]. Classically, PGI 2 exerts its vasodilation through activating PGI 2 receptor coupled to the Gαs protein-adenylyl cyclase pathway to produce cyclic adenosine monophosphate (cAMP) [84,85]. The mechanism underlying H 2 S-induced vasodilation remains not fully understood, potentially involving activation of K + channels [86].…”
Section: Release Of Endothelium-derived Vasodilatorsmentioning
confidence: 99%